Understanding Depressive Symptoms after Bariatric Surgery: the Role of Weight, Eating and Body Image - Sousa, Paula (2014)
Introduction: Depressive symptoms have been reported as prevalent after bariatric surgery. This study aims to analyze the role of weight, eating behaviors and body image in depressive symptomatology in bariatric surgery patients assessed post- operatively.Material and Methods: This is a cross-sectional study including 52 bariatric surgery patients assessed post-operatively with a follow-up time ranging from 22 to 132 months. Psychological assessment included a clinical interview (Eating Disorder Examination) to assess eating disorders psychopathology, and three self-report measures: Outcome Questionnaire 45 – general distress; Beck Depression Inventory – depressive symptoms; and Body Shape Questionnaire – body image.Results: Our data show that depressive symptoms after surgery are associated with loss of control over eating, increased concerns with body image, and body mass index regain. Multiple linear regressions was tested including these variables and showed that body mass index regain after surgery, loss of control over eating and concerns with body image significantly explained 50% of the variance of post-operative depressive symptoms, being the concern with body image the most significant variable: greater dissatisfaction with body image was associated with more depressive symptoms.Discussion: The results of this study showed that a subgroup of patients presents a significant weight gain after bariatric surgery, which is associated with episodes of loss of control over eating, concerns with body image and depressive symptoms.Conclusion: These results stress the relevance of body image concerns after surgery and the importance of clinically addressing these issues to optimize psychological functioning after bariatric surgery.Keywords: Depression; Preoperative Care; Psychiatric Status Rating Scales; Obesity, Morbid; Body Image; Bariatric Surgery.